Navigating the Sea of Online Proctoring - Ng, Susan (Canadian Perspectives on Academic Integrity, 2021)
Education nurtures competency and critical thinking in students, which in turn, lead to the betterment of society. Academic integrity is instrumental in upholding the goal of education. With the rapid pivot to remote teaching and assessment, the incorporation of online proctoring to ensure academic integrity became a necessity. Recognizing some of the causes of academic dishonesty could be magnified with this mode of delivery, the implementation of a student-centred approach to enhance academic honesty with online assessments was embedded in our Practical Nursing math course at Centennial College. Through the use of PowerPoint presentation, demonstrations of strategies and anecdotal stories, I will highlight the complex challenges with online proctoring, the unwitting discoveries of academic breaches, and the multifaceted solutions required. At the end of the formal presentation, an opportunity will be provided for the audience to ask questions, as well as share their experiences. The outcome will be a collect of best practices on how a crew of professors can both support students and keep academic integrity afloat while navigate the uncharted waters of online proctoring on a vessel from an external company offering remote invigilation services.